Catalogue of the type specimens of Yponomeutoidea (Lepidoptera) in the collection of the United States National Museum of Natural History - Sohn, Jae-Cheon; Lewis, Jon A. (Zootaxa, 2012)
The collection of the United States National Museum of Natural History includes 183 type specimens of Yponomeutoidea: 106 holotypes, 24 lectotypes, 2 neotypes and 14 species described from syntypes. The primary type specimens of Yponomeutoidea are catalogued with annotations of their collecting data, specimen condition and, if any, uncertainty involving in the type series. Lectotypes are designated for 23 species comprising six Argyresthiidae: Argyresthia alternatella Kearfott, 1908, A. bolliella Busck, 1907, A. castaneella Busck, 1915, A. furcatella Busck, 1916, A. laricella Kearfott, 1908, A. libocedrella Busck, 1916; two Attevidae: Atteva exquisita Busck, 1912, Oeta comptana var. floridana Neumoegen, 1891; Bedelliidae: Bedellia minor Busck, 1900; two Glyphipterigidae: Abrenthia cuprea Busck, 1915, Glyphipterix semiflavana Issiki, 1930; two Heliodinidae: Lamprolophus lithella Busck, 1900, Scelorthus pisoniella Busck, 1900; three Lyonetiidae: Leucoptera erythrinella Busck, 1900, L. pachystimella Busck, 1904, L. smilaciella Busck, 1900; Praydidae: Eucatagma amyrisella Busck, 1900; three Yponomeutidae: Swammerdamia castaneae Busck, 1914, Zelleria celastrusella Kearfott, 1903, Z. gracilariella Busck, 1904; three putative yponomeutoids: Pliniaca bakerella Busck, 1907, Pl. sparsisquamella Busck, 1907, Podiasa chiococcella Busck, 1900.